Proteolytic profiling and comparative analyses of active trypsin-like serine peptidases in preimaginal stages of Culex quinquefasciatus - Borges-Veloso Andre; Saboia-Vahia Leonardo; Cuervo Patricia; Pires Renata C; Britto Constança; Fernandes Nilma; d’Avila-Levy Claudia M; De Jesus Jose B (Parasites & Vectors, 2012)
Abstract Background The mosquito Culex quinquefasciatu s, a widespread insect in tropical and sub-tropical regions of the world, is a vector of multiple arboviruses and parasites, and is considered an important risk to human and veterinary health. Proteolytic enzymes play crucial roles in the insect physiology including the modulation of embryonic development and food digestion. Therefore, these enzymes represent important targets for the development of new control strategies. This study presents zymographic characterization and comparative analysis of the proteolytic activity found in eggs, larval instars and pupae of Culex quinquefasciatus. Methods The proteolytic profiles of eggs, larvae and pupa of Cx. quinquefasciatus were characterized by SDS-PAGE co-polymerized with 0.1% gelatin, according to the pH, temperature and peptidase inhibitor sensitivity. In addition, the proteolytic activities were characterized in solution using 100 μM of the fluorogenic substrate Z-Phe-Arg-AMC. Results Comparison of the proteolytic profiles by substrate-SDS-PAGE from all preimaginal stages of the insect revealed qualitative and quantitative differences in the peptidase expression among eggs, larvae and pupae. Use of specific inhibitors revealed that the proteolytic activity from preimaginal stages is mostly due to trypsin-like serine peptidases that display optimal activity at alkaline pH. In-solution, proteolytic assays of the four larval instars using the fluorogenic substrate Z-Phe-Arg-AMC in the presence or absence of a trypsin-like serine peptidase inhibitor confirmed the results obtained by substrate-SDS-PAGE analysis. The trypsin-like serine peptidases of the four larval instars were functional over a wide range of temperatures, showing activities at 25°C and 65°C, with an optimal activity between 37°C and 50°C. Conclusion The combined use of zymography and in-solution assays, as performed in this study, allowed for a more detailed analysis of the repertoire of proteolytic enzymes in preimaginal stages of the insect. Finally, differences in the trypsin-like serine peptidase profile of preimaginal stages were observed, suggesting that such enzymes exert specific functions during the different stages of the life cycle of the insect.